Crystal structure of lipid A disaccharide synthase LpxB from Escherichia coli - Thomas E. Bohl (Nature Portfolio, 2018)
LpxB is a membrane-associated glycosyltransferase required for bacterial lipopolysaccharide biosynthesis. Here, Bohl et al. solve the crystal structure of a soluble LpxB variant, showing an intertwined C-terminally swapped dimer, and residues likely mediating association with lipidic substrates or the membrane.